1933
DOI: 10.1113/expphysiol.1933.sp000612
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine in Amphibian Voluntary Muscle

Abstract: 1. Three modifications are suggested in the KOESSLER and HANKE colorimetric technique (based on the Pauli reaction) for the estimation of pyrimidine bases: (a) the substitution of bicarbonate for some of the carbonate in one of the reagents (leading to greater stability in the pigment formed); (b) the use of carnosine nitrate as a standard of reference for estimation instead of a mixture of dyestuffs; and (c) the use of an appropriate light filter in conjunction with the colorimeter. This leads to an eightfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1933
1933
1956
1956

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Recently it has been found that the same statement is true for the amino acid histidine [Eggleton and Eggleton, 1933], but the behaviour of the dipeptide carnosine in similar experiments indicated that only part of the water of the muscle was available to carnosine diffusing in from surrounding saline.This fraction was of the order of 30 p.c. of the total water of the muscle.…”
mentioning
confidence: 81%
“…Recently it has been found that the same statement is true for the amino acid histidine [Eggleton and Eggleton, 1933], but the behaviour of the dipeptide carnosine in similar experiments indicated that only part of the water of the muscle was available to carnosine diffusing in from surrounding saline.This fraction was of the order of 30 p.c. of the total water of the muscle.…”
mentioning
confidence: 81%
“…These figures are corroborated by recent analyses of dog muscle made by Hastings (24). Eggleton (25,26) has shown that certain solutes diffuse through all the water of the frog muscle, while other substances diffuse through only 20 to 30 per cent of the water of vital frog muscle, presumably the extracellular portion. After rigor mortis has set in this selective permeability disappears.…”
Section: Introductionmentioning
confidence: 99%
“…5. This technique has been described by Eggleton et al [1928]. The behaviour of agar gels followed very closely the "square-root law"; the slight but invariable deviations from the law exhibited by living and dead muscles must be attributed to their structure, in so far as it is not accounted for by the [Eggleton et al 1928].…”
Section: Adsorption Of Chloride In Musclementioning
confidence: 95%
“…4. This method has already been used in determining the equilibrium value of creatine [P. Eggleton, 1930], inorganic phosphate [M. G. Eggleton, 1933] and lactate [Ghaffar, 1935] Fig. 5).…”
Section: Adsorption Of Chloride In Musclementioning
confidence: 99%
See 1 more Smart Citation